EFFECTS OF WATER REGIMES AND IRRIGATION FREQUENCIES ON COWPEA GROWTH - Carla E. de Oliveira; André A. do Nascimento; Joaquim M. de Moura Neto; Mateus L. Silva; Carlos N. V. Fernandes; Alexandre R. A. da Silva (Engenharia Agrícola, 2025)
ABSTRACT Cowpea (Vigna unguiculata L.) is a key crop in Brazil's Northeast due to its adaptability to semi-arid conditions. This study evaluated the effects of different water regimes and irrigation frequencies on cowpea cultivation under a semi-arid climate. The experiment was conducted at the experimental area of IFCE – Campus Iguatu-CE, using a randomized block design with 20 treatments and four replications, arranged in a 5 × 4 factorial scheme. The treatments consisted of five water regimes (R1 – 50%, R2 – 75%, R3 – 100%, R4 – 125%, and R5 – 150% of crop evapotranspiration, ETc) and four irrigation frequencies (F1 – daily, F2 – every two days, F3 – every three days, and F4 – every four days). Irrigation was applied via a drip system. The variables evaluated included the number of pods per plant, number of grains per pod, pod length, pod mass, grain yield, and water use efficiency. Results indicated that daily irrigation led to the highest grain yield (381.94 kg ha⁻1) and water use efficiency (1.43 kg ha⁻1 mm⁻1). The most efficient water regime was 407.11 mm (113.7% of ETc), which had a significant isolated effect on pod number, pod mass, and the number of grains per pod.